Single cell sequencing technology and its application in Hypoxic ischemic encephalopathy research. Issue 3 (28th September 2021) - Chen, Ting‐Bao; Zhou, Hong‐Su; Xiong, Liu‐Lin
Abstract : Hypoxic ischemic encephalopathy (HIE) is the common etiology of neonatal morbidity and mortality, which exerts a negative seriously influence for the growth and development of children, and even threatens their life. Therapeutic methods are timely not adopted, it will cause serious irreversible damage to the neonatal nervous system. As no promising therapeutic strategies exist currently, it is important to elucidate the pathological mechanism for HIE, which requires us to explore the nucleic acid molecules, protein, and cell function in HIE patients, and to understand the process of the onset and progression, then research and invent better treatment methods and therapeutic drugs. Single cell sequencing (SCS) exhibits an distinctive advantages in cells research because of the particularity of each cell. This method solves an puzzle about heterogeneit, which could not be solved with multi cell sample research, and provides a new idea and perspective for the un‐elucidated and events further analyzed, such as the behaviors, mechanisms and the relationship between single cell and organism in cell population. It also plays an extremely significant role in the basic research and precision medicine. Some studies have suggested that SCS serves a vital function in the study of HIE. Therefore, this review is aim to elaborate SCS and hypoxic‐ischemic brain injury, and trace the role of microglia in HIE, and prospect its unknown and undiscovered mechanism by SCS.